The clinical and laboratory significance of antiphospholipid syndrome patients in Hospital USM - Nasiruddin, Dhamirah Nazirah Mohd (2021)
Antiphospholipid syndrome (APS) is diagnosed in patients with vascular thrombosis or pregnancy morbidity whose laboratory assays demonstrate persistent antiphospholipid antibodies (aPL). To confirm their existence, these antiphospholipid antibodies, which are lupus anticoagulant (LA), anticardiolipin antibodies (aCL) and anti-β2-glycoprotein I antibodies (anti-β2GPI), need to be repeated after 12 weeks. The objective of this study is to analyse the clinical and laboratory characteristics of patients with confirmed APS sent for LA and aCL tests in Hospital USM. A retrospective study on 391 samples sent for LA tests within 6 years in Haematology laboratory of Hospital USM were analysed. Sixty-nine out of three hundred ninetyone samples showed positivity for LA in the first samples. However only thirty-five repeated sample were available. The results of their aCL tests were also analysed for each patient who were sent for LA testing. Therefore, proportion of confirmed APS patients according to Sydney criteria are 19.5% (17/81). Their result along with clinical and laboratory characteristics of each patient were analysed. Confirmed APS patients (LA or aCL positive) is more common in patients aged between 20-40 years old, female gender with female to male ratio 4.7:1, Malay race, vascular thrombosis, patients with autoimmune diseases such as systemic lupus erythematosus (SLE), normal platelet count, normal prothrombin time (PT), prolonged activated partial thromboplastin time (APTT), normal international normalized ratio (INR), corrected mixing study, prolonged LA-sensitive activated partial thromboplastin time (APTT-LA), positive Rosner’s index, positive DRVVT (LA ratio), positive LA and negative aCL. Multivariate analysis shows prolonged DRVVT ratio (LA ratio >1.2) and positive Rosner’s index were the only independent risk factors responsible for confirmed APS in this study. In conclusion, the number of samples sent for second testing are lesser than the expected amount shows the lack of awareness among healthcare practitioners on the practice of attaining diagnosis of APS on second sample. Therefore, more efforts are needed to be strained to ensure proper investigation of APS.